Orçamento participativo: uma experiência de articulação com poder local e democracia participativa na cidade de Guarulhos (SP) - 2001/ 2011 - Hosokawa, Wagner (2012)
This master thesis addresses the experience of the Participatory Budget (Orçamento Participativo OP) in Guarulhos, an innovative enterprise of popular participation that started in 2001 and was developed during three subsequent mandates of the Workers' Party (Partido dos Trabalhadores PT) in the city. The main research question concerns the ways through which a political project of a democratic mandate articulates with processes of Local Power and Participatory Democracy (2001/2010). The main conceptual references for the research were: Participatory Budget, according to Félix Ruiz Sánchez, Tarso Genro and Ubiratan de Souza; Local Power, according to Édina Evelyn Casali Meireles de Souza, Celso Daniel and Ladislau Dowbor; Participatory Democracy, according to Francisco Oliveira and Leonardo Avritzer, all contemporary authors in the fields of Social Sciences and Social Work. The present study is of qualitative nature, including bibliographic, documental and field work research. This work (i) addresses the historical and political context between 1980 and 2000, period in which social movements emerged in the city; (ii) reorganizes constitutive aspects of the OP in Guarulhos, its implementation and development; (iii) presents conceptual elements that guide the data analysis. The research concludes with a series of reflexions on the importance of including the population in democratic and participatory spaces in articulation with the process of Local Power, in order to enable the construction of new political relations of citizenship. It indicates, therefore, challenges for the consolidation of processes that aim at a more democratic relationship between the civil society and the State